Dan Arnold, Brains, Buddhas, and Believing: The Problem of Intentionality in Classical Buddhist and Cognitive-Scientific Philosophy of Mind - Westerhoff, Jan (Religions of South Asia, 2013)
Dan Arnold, Brains, Buddhas, and Believing: The Problem of Intentionality in Classical Buddhist and Cognitive-Scientific Philosophy of Mind. Columbia: Columbia University Press, 2012. 328 pp. $50.00/£34.50. ISBN: 978-0-231-14546-6 (hardback).